2009
DOI: 10.1007/s00787-009-0750-z
|View full text |Cite
|
Sign up to set email alerts
|

Parental rating of sleep in children with attention deficit/hyperactivity disorder

Abstract: Objective: Sleep problems have often been associated with attention deficit/hyperactivity disorder (ADHD). Parents of those with ADHD and children with ADHD report sleep difficulties more frequently than healthy children and their parents. The primary objective of this paper is to describe sleep patterns and problems of 5 to 11-year-old children suffering from ADHD as described by parental reports and sleep questionnaires. Method: The study included 321 children aged 5–11 years (average age 8.4 years); 45 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
4
23
2
5
Order By: Relevance
“…(Hvolby et al, 2009;O'Brien et al, 2003a;O'Brien et al, 2003b;Owens et al, 2000), whereas other studies report sleep onset problems to be associated with ODD comorbidity and stimulant medication rather than ADHD itself (Corkum et al, 1999;Mick et al, 2000). Higher bedtime resistance in an ADHD population with ODD may exacerbate sleep complaints.…”
Section: Sleep-wake Rhythmsmentioning
confidence: 48%
See 3 more Smart Citations
“…(Hvolby et al, 2009;O'Brien et al, 2003a;O'Brien et al, 2003b;Owens et al, 2000), whereas other studies report sleep onset problems to be associated with ODD comorbidity and stimulant medication rather than ADHD itself (Corkum et al, 1999;Mick et al, 2000). Higher bedtime resistance in an ADHD population with ODD may exacerbate sleep complaints.…”
Section: Sleep-wake Rhythmsmentioning
confidence: 48%
“…With respect to total sleep duration, some authors reported no differences in sleep duration considering clinical samples of children with ADHD and normal controls (Hvolby et al, 2009;Marcotte et al, 1998;Mick et al, 2000), in contrast to other authors who reported both longer (Corkum et al, 2001) and shorter (Owens et al, 2000) sleep duration in ADHD. Several recent studies in larger population samples confirmed that short sleep duration is associated with problems related to attentional control and hyperactivity/impulsivity (Paavonen et al, 2009;Pesonen et al, 2010;Touchette et al, 2009).…”
Section: <Insertmentioning
confidence: 59%
See 2 more Smart Citations
“…Using the subjective parameters, most of the studies have reported sleep disturbances such as early and middle insomnia, nocturnal awakening, short sleep time, restless sleep and daytime sleepiness in children with ADHD [14][15][16] . Even though there is poor understanding of the relationship between sleep and ADHD symptoms, from a clinical standpoint, sleep disturbances associated with ADHD are very relevant since they can cause worsening of ADHD symptoms, leading to an increase in disruptive behaviour 17 .…”
Section: Introductionmentioning
confidence: 99%